Premedication Before Contrast-Enhanced Computed Tomography Scans: A Systematic Review - Ihsan Fahmi Rofananda; Maulana Muhtadin (Talenta Publisher, 2026)
Background: The use of iodinated contrast media (ICM) in Computed tomography (CT) scan improves visualization but carries a risk of hypersensitivity and other adverse reactions. Premedication with corticosteroids and antihistamines is often recommended, though its effectiveness remains debated. Objective: This systematic review aimed to evaluate the efficacy of premedication in reducing adverse reactions to ICM in patients undergoing contrast-enhanced CT. Methods: Following PRISMA 2020 guidelines, a systematic search was conducted in PubMed, ProQuest, and ScienceDirect. Eligible studies included randomized controlled trials, cohort, and case-control studies involving premedication and reporting adverse outcomes after ICM administration. Risk of bias was assessed using the Cochrane RoB tool and Newcastle-Ottawa Scale. Results: Of 2675 records screened, five studies (one RCT and four cohorts; >8,000 exposures) were included. All reported a reduction in adverse reactions with premedication, though protective effects varied. Antihistamines consistently reduced recurrence of mild and late hypersensitivity reactions. Corticosteroids modestly lowered overall reaction rates but were less effective in high-risk patients compared with contrast substitution. One study showed diazepam reduced seizure incidence in glioma patients. Conclusion: In conclusion, Premedication reduces ICM-related adverse reactions, but its benefit depends on patient risk, prior reaction severity, and regimen used. Antihistamines are particularly effective for mild and late reactions, while contrast substitution may outperform corticosteroids in high-risk patients. Keyword: Adverse reactions, Computed tomography, Contrast media, Hypersensitivity, Premedication Latar Belakang: Penggunaan media kontras beryodium (ICM) dalam pemindaian tomografi terkomputasi (CT scan) meningkatkan visualisasi tetapi berisiko menyebabkan hipersensitivitas dan reaksi merugikan lainnya. Premedikasi dengan kortikosteroid dan antihistamin sering direkomendasikan, meskipun efektivitasnya masih diperdebatkan. Tujuan: Tinjauan sistematis ini bertujuan untuk mengevaluasi efikasi premedikasi dalam mengurangi reaksi merugikan terhadap ICM pada pasien yang menjalani CT scan dengan kontras. Metode: Mengikuti pedoman PRISMA 2020, pencarian sistematis dilakukan di PubMed, ProQuest, dan ScienceDirect. Studi yang memenuhi syarat meliputi uji coba terkontrol acak, studi kohort, dan studi kasus-kontrol yang melibatkan premedikasi dan pelaporan hasil yang merugikan setelah pemberian ICM. Risiko bias dinilai menggunakan alat Cochrane RoB dan Skala Newcastle-Ottawa. Hasil: Dari 2675 jurnal yang disaring, lima studi (satu RCT dan empat kohort; >8.000 paparan) diikutsertakan. Semua studi melaporkan penurunan reaksi merugikan dengan premedikasi, meskipun efek perlindungannya bervariasi. Antihistamin secara konsisten mengurangi kekambuhan reaksi hipersensitivitas ringan dan lanjut. Kortikosteroid sedikit menurunkan laju reaksi keseluruhan tetapi kurang efektif pada pasien berisiko tinggi dibandingkan dengan substitusi kontras. Satu studi menunjukkan diazepam mengurangi insiden kejang pada pasien glioma. Kesimpulan: Sebagai kesimpulan, premedikasi mengurangi reaksi merugikan terkait ICM, tetapi manfaatnya bergantung pada risiko pasien, tingkat keparahan reaksi sebelumnya, dan rejimen yang digunakan. Antihistamin khususnya efektif untuk reaksi ringan dan lanjut, sementara substitusi kontras dapat mengungguli kortikosteroid pada pasien berisiko tinggi. Kata Kunci: Hipersensitivitas, Media kontras, Premedikasi, Reaksi yang tidak diinginkan, Tomografi terkomputasi